Analisis Postur Kerja Pada Proses Stitching Karton Box Menggunakan Metode Rapid Upper Limb Assessment (Rula) Pada PT. XYZ - Karenina Karenina; Dene Herwanto (Jurnal Ilmiah Wahana Pendidikan, 2022)
Ergonomics is a discussion of activities that refer to a work system that is healthy, safe, and comfortable for workers. The results of a study by the Ministry of Health in the health profile in Indonesia in 2005 that 40.5% of the illnesses suffered by workers were related to their work for disorders experienced by 9,482 workers in 12 districts/cities in Indonesia, 16% of whom experienced Musculoskeletal Disorders (MSDs). In this research, the object under study is the parts of production at PT. XYZ itself uses the Rappid Upper Limb Assessment (RULA) method and the Nordic Body Maps NBM questionnaire. Based on the results of the NBM questionnaire) the final score of each sewing machine work station with the final score of the first worker is 66 risk level 2 and the second worker gets a final score of 74 and has a risk level of 3. From this risk level, it can be concluded that the highest final score is on the second worker with a risk level of 3 so urgent repair is needed. Based on the results of the assessment of work posture using the RULA method on workers for Table A which consists of the upper arm, forearm, wrist and wrist rotation, the final score is 6. is 5. For Table C the combined final score of Tables A and B is the final score to get 6.